Pelatihan Strategi Problem Based Learning (PBL) Bermuatan Karakter untuk Meningkatkan Keprofesionalan Guru - Evi Purnama Bayu Ningsih; Patri Janson Silaban; Lasma Silaban (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
This socialization activity program involved all Kaloy State Elementary School teachers in Kaloy Village, Tamiang Hulu District, Aceh Tamiang Regency, Aceh Province, totaling 18 teachers. Based on the evaluation in the implementation of this socialization and counseling program, it turned out that the participants who attended this program could be said to have met the target, namely 14 participants came from the 18 targeted participants. Apart from that, all the participants who came also represented classes at the Kaloy State Elementary School Integrated Private Islamic Elementary School in Kaloy Village, Tamiang Hulu District, Aceh Tamiang Regency, Aceh Province. The program for implementing this activity was designed using scientific discussion and question and answer methods. This socialization activity has run smoothly and as expected. The enthusiasm and satisfaction of the participants who attended this community service program were also felt by the presenters. This is proven by the number of participants who attended and there were no participants who were allowed to leave, so it can be said that almost all teachers as participants in this socialization and service activity took part in the entire series of events from the beginning to the end of the activity. Apart from that, the participants also seemed enthusiastic about listening/paying attention to the presentation of material from the presenters and also the discussion and question and answer interactions that occurred during the question and answer session were one indicator or special attraction of the participants towards the material presented by the presenters.